Adaptation of effective international models for regulating the investment activities of ENPFS to the conditions of Kazakhstan - Amirova, B.K.; Meerbekov, Ye.S.; Juchnevicius, E. (Bulletin of the Karaganda University “Law Series”, 2025)
The article is devoted to the legal framework of the investment operation of the Unified Accumulative Pension Fund (UAPF) of the Republic of Kazakhstan. Particular attention is paid to the need for improvement of the current legislation under the conditions of globalization and integration of financial markets. The study offers a comparative analysis of foreign practice in pension asset management in such countries as Norway, Canada, and Australia, where effective models of investment policy have been implemented, ensuring sustainable returns with minimal risks. The possibilities of using these best practices in Kazakhstan’s legal and economic environment are considered. In particular, emphasis is placed on the expansion of the range of investment instruments, the introduction of more liberal asset management company regulations, and the creation of conditions for attracting foreign investors. Special attention is paid to introducing mechanisms for monitoring and assessing the efficiency of investments, including regular audits, risk analysis, and the use of digital technologies. The article also stresses the necessity to raise the level of financial literacy of the population and increase public participation in managing the pension savings. Finally, the article gives recommendations on the modernization of the legal framework, transparency of the investment process, and the elaboration of a complex approach to bringing things into compliance with international standards. These actions, in the long run, should improve the pension system’s financial stability and enhance public confidence in the UAPF.